Managing online creativity for improving innovation performance. Issue 3 (5th June 2017) - Tien, Wen-Pin; Cheng, Colin C.J.
Abstract : Purpose: Building on the socio-cultural theory and the climate literature, the purpose of this paper is to examine: how to effectively manage computer-mediated platforms to improve innovation performance, and which types of computer-mediated platforms firms should be more involved with. Design/methodology/approach: The multivariate mediated regression method and relative effect analysis were employed to test the model. Findings: Analyses reveal that online creative climate mediates the effects of the perceived innovation policy on both novelty and meaningfulness of creative behaviors. In addition, online creative climate is positively related to both radical and incremental innovation performance. Further, the relative performance results of the four types of computer-mediated platforms are found to be unequal. Practical implications: The results suggest to managers that establishing creative climates in computer-mediated platforms is a promising approach to improve firms' innovation performance. The results further indicate that managers should acknowledge the advantages and limitations of each type of computer-mediated platform in order to increase innovation performance. Otherwise, firms may misallocate resources and investment efforts in computer-mediated platforms. Originality/value: By categorizing computer-mediated platforms into four types, this study provides the first synthesis of personal interactions that occur in computer-mediated environments. This study presents the first empirical assessment of how creative climate can be used as a facilitator for improving innovation performance and which type of computer-mediated platforms is more appropriate for radical or incremental innovations.